Model Perkuatan Anyaman Bambu pada Subgrade Bungker Tangki Pendam - Pribadi, Gali; Rumbyarso, Yonas Prima Arga (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
A submersion tank bunker is a storage place for fuel oil tanks at public fueling stations (gas stations). Its function is to localize oil splatters so as not to pollute the soil below if there is a leak in the oil tank. The construction of the submersion tank bunker at the Kelapa Gading gas station in North Jakarta, the basic soil condition is muddy due to low groundwater. This condition is improved by applying a covering layer of bamboo mattress. Bamboo mats are made from wormwood bamboo (Gigantochloa Apus) which is split 5 cm wide each sheet, and then woven to form a woven grid. The presence of groundwater at the bottom of the excavation, drained by pumping out (dewatering). After laying sand, the next step can be casting the bunker concrete floor slab. It is proven that woven bamboo in the form of bamboo mattresses is an alternative to basic soil improvement that can increase the carrying capacity of basic soil effectively.